2015
DOI: 10.3390/toxins7082985
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrogen Peroxide on Different Toxigenic and Atoxigenic Isolates of Aspergillus flavus

Abstract: Drought stress in the field has been shown to exacerbate aflatoxin contamination of maize and peanut. Drought and heat stress also produce reactive oxygen species (ROS) in plant tissues. Given the potential correlation between ROS and exacerbated aflatoxin production under drought and heat stress, the objectives of this study were to examine the effects of hydrogen peroxide (H2O2)-induced oxidative stress on the growth of different toxigenic (+) and atoxigenic (−) isolates of Aspergillus flavus and to test whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(85 citation statements)
references
References 41 publications
7
76
0
Order By: Relevance
“…Previously, we observed that the aflatoxin production capabilities of A. flavus isolates were correlated with the levels of H 2 O 2 stress individual isolates could tolerate or survive32. Here, we found a related trend with isolates with higher stress tolerance and aflatoxin production exhibiting fewer significant DEGs than atoxigenic, less tolerant isolates in both YES and YEP (Table 1).…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Previously, we observed that the aflatoxin production capabilities of A. flavus isolates were correlated with the levels of H 2 O 2 stress individual isolates could tolerate or survive32. Here, we found a related trend with isolates with higher stress tolerance and aflatoxin production exhibiting fewer significant DEGs than atoxigenic, less tolerant isolates in both YES and YEP (Table 1).…”
Section: Discussionsupporting
confidence: 69%
“…Among the atoxigenic isolates, those which are used as biological controls, Aflaguard and AF36, were previously found to tolerate higher levels of oxidative stress than non-adapted isolates including K54A32. In the present study, these biological control isolates exhibited fewer DEGs in comparison to K54A (Table 1).…”
Section: Resultsmentioning
confidence: 47%
See 3 more Smart Citations